GUEST AWARENESS ON SUSTAINABILITY PRACTICES IN ECO-FRIENDLY ACCOMMODATIONS IN SRI LANKA: AN ANALYSIS OF BOOKING.COM REVIEWS - Weerasinghe, I. (The Library, University of Kelaniya, Sri Lanka., 2024)
Sustainable initiatives by eco-friendly hotels ensure the destinations’ environmental, socio-cultural and economic sustainability. The user-generated content (UGC) in online platforms interferes with electronic word of mouth and affects the intention of potential travellers to visit. Booking.com is one of the leading online booking platforms utilized by travellers for efficient reservations in travel and hospitality services. Despite the sustainability efforts practised by eco-friendly hotels, guests’ awareness and perspectives regarding such practices have not been considerably studied. The purpose of this study is to explore the guests’ realization of the sustainable approaches practised by eco-friendly hotels based on their online reviews on the Booking.com platform. The study was constructed as a qualitative research, where secondary data were gathered from reviews of Booking.com. The study is based on 3 ‘sustainability certified’ eco-friendly hotels which indicated the highest number of reviews on Booking.com. A total of 2468 online reviews were available for the selected 3 hotels, while 217 detailed reviews, published from January to July 2024, were considered in data analysis. Following the thematic analysis method, the data were analyzed employing the inductive thematic analysis technique, utilizing the ‘Taguette’ software tool. The study identified 07 themes based on the guests’ insights, including hospitality service and facilities, location and surroundings, negative experience, architectural design, nature-friendly activities, guests’ recommendations, and sustainable practices. The study further emphasizes that the guests’ realization and reflection on the sustainable approaches through online platforms are considerably at an extremely low level compared to their intention to share their lodging experience based on the hospitality service, available facilities and location. The study provides implications for hoteliers in the eco-friendly accommodation sector to be more attentive to improving guests’ realization of sustainable approaches and encouraging them to disseminate authentic experiences through online reviews.
Keywords: Accommodation; Booking.com reviews; Guests’ awareness; Sri Lanka; Sustainability practices